Job stress, co-worker support, role expectation conflict and work-life balance among working women: a quantitative study on multinational companies in Vietnam - Mai, Thuy Duong; Hussain, Ibiwani Alisa; Subramaniam, Anusuiya (The Mattingley, 2020)
Women are increasingly recognizing the importance to maintain the balance between their work and family life. The purpose of this study is to examine the challenges on work-life balance benefits faced by women who are working in multinational companies in Vietnam. The study is intended to unfold the factors influencing female employees who experienced imbalances in their work and life. The study was conducted using a quantitative research technique. A sample of 200 women were randomly selected from multinational companies in Vietnam. The study was intended to gain insights into Vietnamese women with the main advantages that women had made in balancing work life towards expecting high role expectations as a man, productivity must acquire in their work; secondly, life pressure such as work deadline, financial obligations, excessive workloads; finally, their responsibilities that women conception had to strain too much family responsibility, for example, take care of their children, relative relationships and so on. Findings revealed that the three most important issues faced by working women in the multinational companies were related to job stress, co-worker support and role expectation conflict.